ANALISIS PERILAKU HUBUNGAN PELAT-KOLOM TEPI STRUKTUR PELAT DATAR MENGGUNAKAN CONCRETE DAMAGE PLASTICITY (CDP) DALAM ABAQUS - I Ketut Sudarsana; I Gede Gegiranang Wiryadi; I Gede Adi Susila (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2017)
This research was done to investigate the behavior of edge slab-column connection of flat plate structure using the CDP features of ABAQUS software. Experimental specimen obtained in the literature was modelled in ABAQUS software with CDP features to define the concrete inelastic behavior. The investigated slab-column connection is an edge slab-column subassembled connection having slab dimension of 1020 mm x 1540mm, slab thickness of 120 mm, column dimension of 250 mm x 250mm and column height of 1520 mm. The vertical load and unbalanced moment were applied through the column ends. The vertical load works in the direction perpendicular to slab surface, and the unbalanced moment perpendicular to slab free edge that is obtained from a couple of horizontal forces acting in opposite direction. As many as 22 models were analyzed for five variations on CDP parameters and mesh size. The parametric values of the CDP were varied to obtained the analysis results predict well the experimental results. The analysis shows that the parametric values of CDP such as viscosity (µ) of 0,00005, dilatation angle (?) of 40°, using tension strain to define tension behavior of concrete, and considering damage parameter due to compression and tension give the analysis results of the behavior of edge slab-column connections close to experimental result. Key words: edge slab-column connections, unbalanced moment, punching shear, abaqus, concrete damage plasticity